PENDIDIKAN PENYANDANG CACAT DAN SUMBANGANNYA DALAM PEMBANGUNAN NASlONAL - Mumpuniarti Mumpuniarti (LPMPP Universitas Negeri Yogyakarta, 1999)
The essence of the national development is the developmentof the complete Indonesian person and the developmentof the whole Indonesian society. Disabled people aspart of the Indonesian society have to be embraced by developmentsvia education. Education is the main strategyto be used to develop the disabled into the complete Indonesianpersons who are independent, more human, and productive,and whose existence is recognized.Disabled people have difficulties in the course ofdeveloping themselves into persons with such characteristics. The disabled who are deprived of education will causesocial problems and become a burden for society's developments.The problems need to be overcome through educationby means ofa variety of strategies. Those arc developmentof the disabled's potentials, education for the disabledoriented to the labour force, education for the disabledwith future orientations. education which shapes themorality of the disabled, development of the disabled's skillsfor daily life activities, development of the disabled'scomn inication skills, development of vocational trainingfor the disabled, development of the disabled's entrepreneurship,and rehabilitation of the disabled into active participationin the community. Those strategies are intendedto make them independent and more human. Disabled personswho are independent and more human take a part inthe developments and, therefore. contribute to the nationaldevelopment.